Effects of increasing GleptoForte dosage on iron storage and growth in neonatal pigs to 21 days of age - Kamler, Emily; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Due to a lack of transferred Iron from sow to piglet, neonatal pigs are susceptible to iron deficiency, caused by rapid growth in the first 21 days of age. Lack of iron causes low RBC count, lethargy, and, ultimately, mortality. Common iron supplementation in baby piglets may be able to be replaced by supplementation of Gleptoforte, and injectable supplement containing gleptoferron. This study was conducted to evaluate the effects of varying dosages of Gleptoforte in neonatal pigs. 336 piglets, from 28 litters were randomized into treatment pens, with two pens per treatment, half intact male, half female, totaling 56 piglets per treatment. There was a total of six treatments: Neg. Control receiving no injection, 50, 100, 150, 200, 200mg plus 100mg booster at day 11 in nursery. Each mL of Gleptoforte contains 200mg of iron, thus, dosages were 0, 0.25, 0.50, 0.75, 1.0, 1.0 plus 0.50mL, respectively. One barrow per treatment, per litter was used for blood collection at days 3, 11, and 21 of life. Blood samples were evaluated for Hemoglobin(Hgb), Hematocrit(Hct), Serum Fe, and Total Iron Binding Capacity(TIBC). Weights from the same units were taken at days 3, 11, and 21 of life. Consumption of lactation feed was also evaluated by weight, with the feed containing 110mg/kg of iron from ferrous sulfate. Overall, increasing Gleptoforte dosage increased ADG of piglets, however, the treatment with an added booster did not see any improvement in gain compared to the equivalent treatment, without. However, differences between blood parameters of the 200mg and 200 +100mg treatments were observed, with the latter having the highest Hgb count. Although the 200+ 100mg dosage saw Hgb increase, it also saw the highest Hct values at weaning. There was little to no observable differences in Serum Fe and TIBC measurements in the 200mg and 200 + 100mg treatments. It was determined that a treatment of no iron injection is by far the most detrimental to growth and health. Although the administration of the 200 +100mg dosage showed improvement in hematological factors compared to 200mg dosage, there was no observable influence of the 200 +100mg dose on growth performance.
Keywords: Fall 2017